Optimization of Speaking Ability in Early Childhood - Manurung, Ade Karunia Rizky (Early Childhood Research Journal (ECRJ), 2019)
abstract :Speech ability is a person's ability to express, convey, express and say something that is in someone's thoughts and feelings. The ability to speak has an important role in the success of socializing someone, because through speaking skills one can communicate and interact with people around him. This study aims to minimize speech delays in early childhood by optimizing learning in early childhood by stimulating children through learning media and adding literature to improve speaking skills in early childhood.Â